2004
DOI: 10.1210/jc.2003-030907
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Growth Hormone Deficiency in Pediatric-Onset Langerhans Cell Histiocytosis: Efficacy and Safety of Growth Hormone Treatment

Abstract: We retrospectively studied 61 patients with GH deficiency (GHD), identified among 589 patients with Langerhans cell histiocytosis (LCH) enrolled in a nationwide survey between 1993 and 2001. Overall, 141 patients in the survey developed diabetes insipidus. The median follow-up of the 61 patients with GHD was 12 yr. The 5- and 10-yr risks of GHD among patients with diabetes insipidus were 34.7 +/- 4.5% and 53.7 +/- 5.2%, respectively. Growth velocity decreased soon after LCH diagnosis in patients who developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 21 publications
4
43
0
1
Order By: Relevance
“…The unexpected observation of ADH as the sole additional deficiency in nine patients may relate to the association of ADH deficiency and histiocytosis (21), and MRI may potentially identify the structural lesion in such cases (22). Patients with additional pituitary deficiencies diagnosed during follow-up had a higher incidence of breech presentation, perinatal asphyxia, and neonatal complications, and a trend toward greater delivery complications.…”
Section: European Journal Of Endocrinologymentioning
confidence: 94%
“…The unexpected observation of ADH as the sole additional deficiency in nine patients may relate to the association of ADH deficiency and histiocytosis (21), and MRI may potentially identify the structural lesion in such cases (22). Patients with additional pituitary deficiencies diagnosed during follow-up had a higher incidence of breech presentation, perinatal asphyxia, and neonatal complications, and a trend toward greater delivery complications.…”
Section: European Journal Of Endocrinologymentioning
confidence: 94%
“…Growth hormone deficiency is the most frequent additional deficit, accounting for 42% of cases with CDI and LCH. The 10-year cumulative incidence of growth hormone deficiency among patients with CDI in the French nationwide LCH survey was approximately 54% [38]. The identification of circulating AVPc-Abs in LCH patients and their tendency toward spontaneous clearance [24,25] suggest that these autoantibodies might be an LCH-related immune epiphenomenon.…”
Section: Acquired Forms Of CDImentioning
confidence: 99%
“…Compared with historical controls, the subjects on GH did not appear to have an increased number of recurrences. Most recently, Donadieu et al [27]reported on 61 subjects with LCH treated with GH from the French LCH Study Group. Among those with pituitary involvement, the number of recurrences were similar between those treated with GH and those who were not.…”
Section: Cancer Risk and Gh Therapymentioning
confidence: 99%